Anti-biofilm activity of hydromethanolic plant extracts against Staphylococcus aureus isolates from bovine mastitis. Issue 5 (May 2019) - Gomes, Fernanda; Martins, Natália; Ferreira, Isabel C.F.R.; Henriques, Mariana
Abstract: Bovine mastitis (BM) presents a high incidence, being Staphylococcus aureus one of the major causative agents. Antibiotics comprise the most common therapeutic approach, but due to their indiscriminate use, high rates of increasingly resistant bacterial species have been markedly pointed out. Particularly, S. aureus possesses a pronounced ability to form biofilms, and therefore, are of pivotal interest due to its alarming pathogenicity. The present study investigates the antibacterial properties of Eucalyptus globulus methanol: water extracts, alone and in combination with Juglans regia, against S. aureus isolates from BM. All isolates and reference strain proved to be good biofilm producers after 24 h of bacterial growth. Individually, the studied plant extracts (PE) lead to a considerable biofilm cells reduction, but their combination revealed to be the most effective strategy. When tested in combination, both extracts led to a 3 and 5 log reduction for S. aureus ATCC 25923 and S. aureus 1, respectively. Based on these findings, both PE seem to be promissory antimicrobial agents for upcoming use on dairy industry contaminations, BM and even S. aureus -triggered food poisoning. Further studies are needed to understand which of the compounds present in the extracts are responsible for the observed effects, including their corresponding modes of action.